MANFAAT PENAMBAHAN TEPUNG KUNYIT (Curcuma domestica Val) DAN TEPUNG JAHE (Zingiber officinale) TERHADAP KUALITAS BAKSO ITIK AFKIR DENGAN LAMA PENYIMPANAN YANG BERBEDA - Indah Nur Lestarini; Novitasari Anggarawati; Adi Magna Patriadi Nuhriawangsa; Ratih Dewanti (Faculty of Animal Science, Universitas Gadjah Mada, 2015)
The aim of the research was to determine the advantage of tumeric flour (Curcuma domestica Val) and ginger flour (Zingiber officinale) addition on quality of culled duck meatball in different storage times. The materials were thigh duck, tumeric flour and ginger flour. The design used in experiment was a Completely Randomized Design (CRD) with factorial pattern 4x3 as the first factor was concentration of turmeric flour (0; 0.5; 1.0; 1.5%) and ginger flour (0; 1; 2; 3%) and the second one was storage time (0; 8; 16 hours). The result of the research showed that storage time affected (P<0.05) pH, tenderness and waterholding capacity. Concentration of tumeric flour and ginger flour affected tenderness.There was no interaction between those two factors on pH, water-holding capacity, tenderness,and total proteolitic bacteria. Concentration of turmeric flour 0,5% and ginger flour 1% with storage time during 0 hours gave the best result, with a pH value 6.49, tenderness 0.31, water-holding capacity 22.27, and a total proteolytic bacteria , 3.57x104. In conclusion, the finest result founded at 0.5% of turmeric flour and 1% of ginger flouraddition in meatball before storage.(Keywords: Culled duck, Ginger flour, Meatball, Storage time, Tumeric flour)